Murine AIDS is an antigen-driven disease: requirements for major histocompatibility complex class II expression and CD4+ T cells. - Giese, N A (1994)
Murine AIDS (MAIDS) is a complex syndrome of lymphoproliferation and immunodeficiency induced by a replication-defective murine leukemia virus (BM5def) that encodes Pr60gag as its only product. It has been suggested that the gag polyprotein is responsible for vigorous antigenic stimulation of CD4+ T cells and generalized secondary activation of the immune system. This model was tested first by infecting mice (C2K/O) that lack class II major histocompatibility complex molecules required for presentation of antigens to CD4+ T cells. C2K/O mice expressed BM5def at high levels but did not develop MAIDS either when unmanipulated or following transfer of CD4+ T cells. Second, B6 mice reconstituted with C2K/O bone marrow cells had normal frequencies of B cells (class II negative) and CD4+ cells and expressed high levels of BM5def transcripts but did not develop MAIDS; however, MAIDS developed in class II-competent nu/nu mice reconstituted with CD4+ T cells and in C2K/O mice reconstituted with B6 bone marrow to give class II-positive B cells and with purified CD4+ T cells. These results indicate that induction of MAIDS by BM5def is antigen driven and is dependent on expression of major histocompatibility complex class II molecules on antigen-presenting cells and the presence of CD4+ T cells.